2014
DOI: 10.1007/s13670-014-0106-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Management of the Geriatric Urologic Oncology Patient

Abstract: The geriatric population presents a unique set of challenges in urologic oncology. In addition to the known natural history of disease, providers must also consider patient factors such as functional and nutritional status, comorbidities and social support when determining the treatment plan. The development of frailty measures and biomarkers to estimate surgical risk shows promise, with several assessment tools predictive of surgical complications. Decreased dependence on chronologic age is important when ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…Traditionally, clinicians have used coarse measurements of functional status, including the Charlson Comorbidity Index and the Eastern Cooperative Oncology Group performance measure, to help to guide decisions. Although these measurements are valuable risk‐assessment tools, they lack the ability to quantify subclinical physiologic deficits and cognitive disability . More focused measures of functional status, such as the activities of daily living (ADLs), physical component summary (PCS) score, proxy survey response, and mental component summary (MCS) score, can predict adverse outcomes across a wide spectrum of diseases .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, clinicians have used coarse measurements of functional status, including the Charlson Comorbidity Index and the Eastern Cooperative Oncology Group performance measure, to help to guide decisions. Although these measurements are valuable risk‐assessment tools, they lack the ability to quantify subclinical physiologic deficits and cognitive disability . More focused measures of functional status, such as the activities of daily living (ADLs), physical component summary (PCS) score, proxy survey response, and mental component summary (MCS) score, can predict adverse outcomes across a wide spectrum of diseases .…”
Section: Introductionmentioning
confidence: 99%
“…Although these measurements are valuable riskassessment tools, they lack the ability to quantify subclinical physiologic deficits and cognitive disability. 8 More focused measures of functional status, such as the activities of daily living (ADLs), physical component summary (PCS) score, proxy survey response, and mental component summary (MCS) score, can predict adverse outcomes across a wide spectrum of diseases. [9][10][11][12] Although clinicians who manage prostate cancer generally do not assess these measures of functional status, they may indirectly account for them in their overall gestalt about a patient's condition, 13 which ultimately influences their treatment recommendation.…”
Section: Introductionmentioning
confidence: 99%
“…Staehler et al [ 20 ] analyzed 117 patients with renal cancer who underwent surgical treatment and found that the incidence of perioperative complications of partial nephrectomy and radical nephrectomy was 12% and 15%, respectively, and the incidence of complications within 30 days was 4% and 7%, with no significant difference. However, Sun et al [ 21 ] found that there were more complications in elderly patients over 75, and death was mostly due to cardiovascular and cerebrovascular diseases and non-tumor causes. Many studies support nephron-sparing surgery for elderly patients [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] Prostate cancer has a wide variety of treatments, including radical prostatectomy or other conservative measures, like radiotherapy and hormone therapy. 11,12 Robot-Assisted Radical Prostatectomies (RARP) have become a popular treatment option for prostate cancer as RARP decrease blood loss and the rates of complications when compared to open prostatectomies. 13 Because the incidence of prostate cancer remains high, in tandem with the increase in number of RARP performed, analyzing frailty with RARP could prove worthwhile.…”
Section: Introductionmentioning
confidence: 99%